DIGITAL LITERACY EDUCATION ON INFORMATION IN MENTAL HEALTH ISSUES IN STUDENTS OF SMAN 1 MARGAASIH, BANDUNG REGENCY - Asri Fitrananda, Charisma; Muhammad Yusuf, Yogi; Swastikawara, Sinta; Bahtiar, Yusuf; Avila Justine Kalalo, Clairene (STAI Al-Hidayah Bogor, 2024)
Excessive and unwise use of social media among adolescents has become a serious concern regarding its impact on mental health. Various studies show that uncontrolled use of social media can trigger various problems such as low self-esteem, depression, anxiety, and even the desire to end life. In response to this, the community service team designed a mentoring program to equip school students with the knowledge and skills to use social media wisely. In this program, students will gain an in-depth understanding of the negative impact of uncontrolled social media use. They will also be trained to manage their time and manage their social media use, think critically in assessing online content, and manage emotions and stress related to social media activities. In addition to providing materials, the program also provides simulation sessions where students can practice wise strategies in dealing with various scenarios of social media use. Through this comprehensive mentoring program, it is hoped that students can acquire adequate skills to use social media wisely. Thus, they can avoid various mental health problems that often arise due to uncontrolled use of social media. The results of this program are expected to make a significant contribution to efforts to maintain the mental health of adolescents in today's digital era.